Quelles balises curriculaires en éducation à la prospective territoriale durable ? Valeurs d’émancipation et finalités d’implications politiques des jeunes dans les études de cas en géographie - Angela Barthes; Sylviane Blanc-Maximin; Elisabeth Dorier (Éducation et Socialisation)
Sustainable education projects (Lange, 2012, 2017, Barthes, 2017) or territories (Dussault, 2017, Hucy, 2017) offer educational opportunities with emancipatory and civic aims. We propose assessment tools to teachers involved in "educations for" in the form of curriculum tags. It is a question of promoting collective management of the public affairs of young people without introducing into individual behavioral normalisations. The curriculum guidelines are based on the epistemological framework of "educations for", that of critical thinking, and on an adaptation of the common base of knowledge of skills and culture (MEN, 2015). We examine 88 territorial prospective projects (592 students) carried out in 19 high school classes (Dorier, Rouquier, Valegeas, 2017). The results focus on students' abilities to problematize, identify social issues, position themselves against a coherent polis (Audigier, 2017), adopt a critical posture. The questions are posed differently in relation to the problems usually raised in didactics of the disciplines. What place for scientific knowledge ? What is the relationship to local areas that invite themselves to school, to past and future temporalities (Vergnolle-Mainar, 2017). What awareness of sustainability issues to think creatively about the future (Pache, Hertig, Curnier, 2016) ? What does face-to-face confrontation allow ? We postulate that reconnecting with the real balance of power between the uses and the actors of a concrete territory is very far from the instrumental "common" (of antipolitical nature) of the hidden curriculum of ESD (Barthes, 2018). The student faces a concrete problem and with the curricular tags increases his apprehension of politics and therefore of citizen action.